AI Integration in E-Learning for Vocational Education Effectiveness - Didi Kurnaedi (bit-Tech, 2025)
The development of digital technology has had a significant impact on the world of education, particularly through the use of e-learning systems. This online learning model provides flexibility, accessibility, and efficiency in the teaching and learning process. However, the main challenges still faced are the lack of interactivity, limited personalization of learning, and the difficulty in adapting materials to student needs in vocational education, which emphasizes practical aspects and skills. The presence of Artificial Intelligence (AI) offers new opportunities to overcome these limitations. With its data analysis capabilities, adaptive learning, and automation, AI can help create more relevant, contextual, and effective learning experiences. This study aims to analyze the integration of artificial intelligence (AI) in e-learning systems to improve learning effectiveness in vocational education. The method used is a sequential explanatory mixed methods design, implemented in two phases. The quantitative phase involved 375 vocational high school student respondents in the Tangerang area through a questionnaire, while the qualitative phase explored the findings through in-depth interviews and observations at 22 selected participating schools. The results show that the use of AI can personalize materials according to student needs, provide automated learning recommendations, create chatbot-based virtual assistants, and support evaluation with an intelligent system. The positive impact of implementing AI in e-learning is increased learning motivation, student engagement, and their readiness to face industry demands. Therefore, integrating AI into e-learning systems can be an effective strategy to strengthen the quality of vocational education. Based on these findings, the study recommends the need to improve digital infrastructure readiness, strengthen teachers' technological competencies, and develop clear regulations regarding the security and ethical use of student data. Implementing supporting policies and ongoing training programs for educators is crucial to maximize the potential of AI and ensure its equitable and sustainable implementation in vocational education environments.